FEMINISM BASED ON THE HEGEMONY OF GENDER FOUND IN THE AUTOBIOGRAPHY OF GADIS ARIVIA - Hidayatul Munawaroh; Sulistyaningsih Sulistyaningsih (JournEEL, 2023)
Abstract Women have the right to obtain higher education and other rights as men. This study about "Feminism Based On The Hegemony of Gender Found In The Autobiography of Gadis Arivia” focuses on the analyzes of the Autobiography of Gadis Arivia book, it is about hegemony of gender. The purpose of this article is to analyze the hegemony of Gadis Arivia Book. A descriptive-qualitative methodology was employed in this investigation. Documentation and library research are used in this approach of study. The population of the study is the readers of the Gadis Arivia book, and the study's sample is its reflection section. The analysis shows that this interesting story is full of efforts to fight for women's emancipation so that they are equal to men.